2003
DOI: 10.1016/s0266-7681(02)00305-4
|View full text |Cite
|
Sign up to set email alerts
|

Palmar Cortical Angle of the Distal Radius: A Radiological Study

Abstract: Fifty lateral radiographs of normal wrists were viewed to determine the palmar cortical angle of the distal radius. The palmar cortical angle is different to its previously described palmar tilt or angulation. The mean value for the palmar cortical angle was 37 degrees (range, 26-50 degrees). This may be clinically important in the design of palmar plates for the distal radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…As positioning of the plate is closely related to the volar surface anatomy of the distal radius, VCAs of the volar radius should be important anatomic parameters for proper plate placement. Bassi et al (2003) measured the VCA of 50 normal lateral wrist radiographs; they reported a mean VCA of 37.1°. Agir et al (2014) measured the VCA in 18 dried adult cadaver radii using the lateral radiographic images; they reported that the mean value was 37.7°.…”
Section: Discussionmentioning
confidence: 99%
“…As positioning of the plate is closely related to the volar surface anatomy of the distal radius, VCAs of the volar radius should be important anatomic parameters for proper plate placement. Bassi et al (2003) measured the VCA of 50 normal lateral wrist radiographs; they reported a mean VCA of 37.1°. Agir et al (2014) measured the VCA in 18 dried adult cadaver radii using the lateral radiographic images; they reported that the mean value was 37.7°.…”
Section: Discussionmentioning
confidence: 99%
“…The palmar cortical angle was described in a radiographic study by Bassi et al The mean values for the palmar cortical angle in 50 radiographs of healthy wrists were measured at 37°(range 26°-50°) [32]. The different default angles of precontoured plates may not address the palmar cortical angle sufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The PCA was defined at the angle made by the intersection of two lines-(A) along the volar aspect of the radial shaft and (B) along the volar tilted portion of the distal radius ( Figure 1). 7 A higher PCA corresponds to lesser curve on the volar aspect of the distal radius. As well as PCA, other patient data collected included age and gender.…”
Section: Methodsmentioning
confidence: 99%